2019
DOI: 10.3390/app9163234
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Rock-Like Specimens with Single Flaw under Hydro-Mechanical Coupling

Abstract: Featured Application: To study the mechanical properties and cracking behavior of jointed rock mass under hydro-mechanical coupling, a series of uniaxial compression tests, and conventional and hydraulic coupled triaxial compression tests were carried out on cylinder gypsum specimens with a single pre-existing flaw. Based on X-ray computed tomography (CT) and scanning electron microscope (SEM) observation, the mechanical properties and crack behavior were analyzed. The results could provide a useful reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Xing et al injected water pressure into the rock surface with pre-existing defects, and observed the distribution range and shape size of cracks by CT and SEM techniques. After analysis, it is found that the water pressure will accelerate the further expansion of the original crack, and the main form of force is expressed as tension 15 . Researching on the change of rock strength based on different immersion durations, Zhu et al took gypsum rock as the experimental rock sample, performed conventional compression and electronic microscopic tests on rock samples under different immersion durations.…”
Section: Introductionmentioning
confidence: 99%
“…Xing et al injected water pressure into the rock surface with pre-existing defects, and observed the distribution range and shape size of cracks by CT and SEM techniques. After analysis, it is found that the water pressure will accelerate the further expansion of the original crack, and the main form of force is expressed as tension 15 . Researching on the change of rock strength based on different immersion durations, Zhu et al took gypsum rock as the experimental rock sample, performed conventional compression and electronic microscopic tests on rock samples under different immersion durations.…”
Section: Introductionmentioning
confidence: 99%
“…The strain component can be determined by analyzing the X-ray radiation signal in different directions, i.e., at angles Ψ and Ψ. Based on this basic principle, a numerical analysis was developed to obtain tomographic images of stressed materials in recent reports [36][37][38][39]. X-ray computed tomography was further extended to evaluate mechanical performance and defects.…”
Section: Introductionmentioning
confidence: 99%
“…Youssef et al [40] and Patterson et al [36] investigated the stress-strain property of polymers by X-ray tomography. They used a finite element method to model and in-situ test to validate elastic and hyper-elastic deformation properties of polymers under compression; Fieres et al focused on the new technology of 3D printing and used X-ray to test the failure possibility of printed parts [37]; Xing et al inspected jointed rocks with X-ray and scanning electron microscope to find evidence of cracks under mechanical compression [39]. Although X-ray diffraction provides sensitive, reliable and quantitative stress-strain measurements and usually acts as a reference, such radiographic NDT has the obvious disadvantage of complicated instrumentation and harmful ionizing radiation which requires high level of operation and testing standards.…”
Section: Introductionmentioning
confidence: 99%
“…Using a coupled thermal-hydro-mechanical test system, Li et al (2018) tested single-fracture red sandstone specimens under three-dimensional stress and evaluated the energy and crack propagation rate. Using a GCTS RTX-3000 triaxial rock testing system, Zhou et al (2018) and Xing et al (2019) applied axial pressure, confining pressure, and water pressure to prefabricated single-crack rock samples and analyzed the stress-strain and crack evolution characteristics of the crack bodies under hydraulic action. To study fracture and fissure development in rock, Mei et al (2019) prepared a threedimensional cylindrical test piece and applied axis pressure and water pressure to the rock body using a servo-controlled RLW-1000G rock rheology testing system.…”
Section: Introductionmentioning
confidence: 99%